Negative plate and lithium ion battery

By designing the optimized negative electrode current collector layer and negative electrode active material layer in the negative electrode sheet of the lithium-ion battery, the volume expansion problem of silicon-based materials during charging and discharging is solved, the tensile strength and elongation of the electrode sheet are improved, and the service life of the battery is extended.

CN119764326AActive Publication Date: 2025-04-04ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411817685.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The volume expansion and contraction of the silicon-based material during the charging and discharging of the negative electrode sheet of the existing lithium-ion battery leads to distortion, deformation and fracture of the electrode sheet, thereby accelerating the expansion failure of the battery and the rapid attenuation of the cycling performance.

Method used

A negative electrode sheet is designed, which includes a negative electrode current collector layer and a negative electrode active material layer arranged in sequence. The negative electrode active material layer contains a silicon-based material. By adjusting the thickness, grain size ratio and the blending ratio of the negative electrode current collector layer, it satisfies a specific relationship to improve the tensile strength and elongation of the electrode sheet and alleviate the expansion stress of the silicon-based material.

Benefits of technology

By optimizing the structure of the negative electrode sheet, it significantly improves its mechanical reliability during the charging and discharging process, avoids fracture and deformation of the electrode sheet, extends the service life of the battery, and improves the circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182274970000071
    Figure BDA0005182274970000071
  • Figure BDA0005182274970000081
    Figure BDA0005182274970000081
Patent Text Reader

Abstract

The invention discloses a negative plate and a lithium ion battery. The negative electrode plate comprises a negative electrode current collector layer and a negative electrode active substance layer which are sequentially arranged, the negative electrode active substance layer comprises a negative electrode active substance, the negative electrode active substance comprises a silicon-based material, and the negative electrode plate meets the formula I: (31.7 lambda + 15) / (2930W) is greater than or equal to 0.2 and less than or equal to 7.5. The expansion stresses generated by different silicon doping proportions in the negative electrode material are different, the thickness grain size ratio lambda is closely related to the tensile strength and the ductility, and when the thickness grain size ratio is increased, the tensile strength is increased, and the ductility is reduced; and when the thickness grain size ratio is reduced, the tensile strength is also reduced, and the ductility is increased. Therefore, the pole piece has good tensile strength and ductility, can cope with expansion stress caused by a silicon-based material, effectively limits expansion and deformation of the silicon-based material in XY directions during charging and discharging, avoids breakage of the pole piece, maintains the cycle performance of the pole piece, and prolongs the service performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to negative electrode sheets and lithium-ion batteries. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, no memory effect, long cycle life, fast charge and discharge, and low self-discharge. They are widely used in consumer electronics, electric vehicles, energy storage and other fields. Among them, the choice of negative electrode active materials is directly related to the energy density of lithium-ion batteries, and also affects the rate performance. Thanks to the advantages of low lithium insertion potential, high theoretical specific capacity, price and environmental friendliness, graphite materials are currently the main choice for negative electrode active materials for lithium-ion batteries. However, as the market demand for the energy density and charging rate of lithium-ion batteries increases, graphite materials alone can no longer meet today's needs.

[0003] At present, a common method to improve energy density is to increase the proportion of silicon-based materials in the negative electrode active material. However, during the charging and discharging process, lithium ions will be embedded in and out of the negative electrode active material mixed with silicon-based materials, causing the volume of the silicon-based material to expand and contract. This phenomenon is more obvious for a high proportion of silicon doping. The serious volume change of silicon-based materials during the cycle process produces a large expansion force on the pole piece. The expansion force in the X and Y directions causes the pole piece to twist and the battery appearance to deform, thereby accelerating the expansion failure, and severe lithium precipitation will occur in the deformed area; even the pole piece will break near the corner position, the internal resistance will increase significantly, and the cycle performance will decay rapidly. Therefore, it is necessary to provide a negative electrode sheet that can more effectively alleviate the volume expansion of silicon particles, improve the mechanical reliability of the pole piece, and take into account the cycle performance. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a negative electrode sheet and a lithium-ion battery.

[0005] In a first aspect of the present application, a negative electrode sheet is provided, the negative electrode sheet comprising a negative electrode current collector layer and a negative electrode active material layer arranged in sequence, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising a silicon-based material, and the negative electrode sheet satisfies Formula I: 0.2≤(31.7λ+15) / (2930W)≤7.5;

[0006] Wherein, λ = T / D, T is the thickness of the negative electrode current collector layer, and D is the grain size of the negative electrode current collector;

[0007] W is the mass percentage of silicon-based material in the negative electrode active material.

[0008] The negative electrode sheet according to the first aspect of the present application has the following beneficial effects:

[0009] Different silicon doping ratios in negative electrode materials produce different expansion stresses, and the thickness grain size ratio λ is closely related to tensile strength and elongation. When the thickness grain size ratio increases, the tensile strength increases and the elongation decreases; conversely, when the thickness grain size ratio decreases, the tensile strength also decreases, while the elongation increases. Under the condition of satisfying the above relationship, the pole piece has good tensile strength and elongation, can cope with the expansion stress caused by silicon-based materials, effectively limit the expansion and deformation of silicon-based materials in the XY direction during charging and discharging, avoid pole piece breakage, maintain its cycle performance, and extend battery performance.

[0010] In some embodiments of the present application, 1<λ≤40, and λ can be, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 15, 16, 18, 20, 22, 24, 25, 26, 28, 30, 32, 34, 35, 36, 38, or 40.

[0011] In some embodiments of the present application, T is 4 to 9 μm, and T may be, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or 9 μm.

[0012] In some embodiments of the present application, D is 0.1-3.8 μm, and D can be, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0. 6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1 .7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm.

[0013] In some embodiments of the present application, 3%≤W≤30%, and W can be, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%.

[0014] In some embodiments of the present application, the negative electrode sheet also satisfies Formula II: 0.4≤(18W+42) / C≤0.9;

[0015] Wherein, C is the elastic modulus of the negative electrode current collector layer.

[0016] The elastic modulus is a physical property of the current collector, which describes the ability of the current collector to deform elastically. The higher the elastic modulus of the current collector, the better the elastic deformation ability of the current collector, and the stronger the recovery ability after being subjected to the expansion force. Therefore, when the above relationship is met, the pole piece will be softer and have better mechanical reliability, thereby avoiding breakage or deformation during the cycle process, thereby slowing down capacity attenuation and thickness expansion.

[0017] In some embodiments of the present application, 50 GPa≤C≤120 GPa, and C can be, for example, 50 GPa, 55 GPa, 60 GPa, 65 GPa, 70 GPa, 75 GPa, 80 GPa, 85 GPa, 90 GPa, 95 GPa, 100 GPa, 105 GPa, 110 GPa, 115 GPa, or 120 GPa.

[0018] In some embodiments of the present application, the tensile strength of the negative electrode current collector layer is 250-900 MPa, for example, it can be 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa, 550 MPa, 600 MPa, 650 MPa, 700 MPa, 750 MPa, 800 MPa, 850 MPa, or 900 MPa.

[0019] In some embodiments of the present application, the elongation of the negative electrode current collector layer is 2-15%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.

[0020] In some embodiments of the present application, the silicon-based material includes at least one of elemental silicon, silicon-carbon material, silicon-oxygen material, and silicon alloy.

[0021] In some embodiments of the present application, the silicon alloy includes an alloy formed by silicon and at least one metal element such as iron, cobalt, nickel, copper, zinc, magnesium, germanium, lithium, silver, and aluminum.

[0022] In some embodiments of the present application, the silicon-based material includes a silicon core and a shell covering the silicon core, the silicon core includes at least one of elemental silicon, silicon-carbon material, silicon-oxygen material, and silicon alloy, and the shell includes a carbon coating layer.

[0023] In some embodiments of the present application, the mass of the carbon coating is 1 to 50% of the total mass of the carbon coating and the silicon oxide particles, for example, it can be 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%.

[0024] In some embodiments of the present application, the negative electrode current collector layer contains at least one metal element of copper, nickel, and titanium.

[0025] In some embodiments of the present application, the negative electrode current collector layer includes a metal foil.

[0026] In some embodiments of the present application, the metal foil has a porous structure.

[0027] In some embodiments of the present application, the negative electrode sheet includes a first negative electrode current collector layer and a second negative electrode current collector layer, a polymer layer is provided between the first negative electrode current collector layer and the second negative electrode current collector layer to form a composite current collector. A first negative electrode active material layer is provided on a side of the first negative electrode current collector layer away from the second negative electrode current collector layer, and a second negative electrode active material layer is provided on a side of the second negative electrode current collector layer away from the first negative electrode current collector layer.

[0028] In some embodiments, the first negative electrode active material layer and the first negative electrode current collector layer satisfy Formula I, λ is the ratio of the thickness of the first negative electrode current collector layer to the grain size, and W is the mass percentage of the silicon-based material in the first negative electrode current collector layer to the active material in the first negative electrode active material layer. In some embodiments, the second negative electrode active material layer and the second negative electrode current collector layer satisfy Formula I, λ is the ratio of the thickness of the second negative electrode current collector layer to the grain size, and W is the mass percentage of the silicon-based material in the second negative electrode current collector layer to the active material in the second negative electrode active material layer.

[0029] In some embodiments, the first negative electrode active material layer and the first negative electrode current collector layer satisfy Formula II, W is the mass percentage of the silicon-based material in the first negative electrode current collector layer to the active material in the first negative electrode active material layer, and C is the elastic modulus of the first negative electrode current collector layer. In some embodiments, the second negative electrode active material layer and the second negative electrode current collector layer satisfy Formula II, W is the mass percentage of the silicon-based material in the second negative electrode current collector layer to the active material in the second negative electrode active material layer, and C is the elastic modulus of the second negative electrode current collector layer.

[0030] In some embodiments of the present application, the raw material of the negative electrode active material layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.

[0031] In some embodiments of the present application, the negative electrode active material layer includes 70 to 99 wt % of the negative electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.

[0032] In some embodiments of the present application, when the negative electrode active material, the conductive agent and the binder are made into the negative electrode active material layer, the active material, the conductive agent and the binder are dispersed in a solvent and then coated on the negative electrode current collector layer, and dried to obtain the negative electrode active material layer.

[0033] The present application also relates to a method for preparing a negative electrode sheet, the method comprising the following steps:

[0034] The negative electrode active material slurry is coated on the negative electrode current collector to form a negative electrode sheet.

[0035] In some embodiments of the present application, the slurry of the negative electrode active material includes the negative electrode active material and at least one of a conductive agent and a binder. In some specific embodiments, the slurry of the negative electrode active material also includes a solvent.

[0036] In some embodiments of the present application, the method of coating the slurry of the negative electrode active material includes at least one of spraying, dipping, blade coating, transfer coating, extrusion coating, cast coating, micro-gravure coating, and the like.

[0037] In a second aspect of the present application, a lithium-ion battery is provided. The lithium-ion battery comprises the aforementioned negative electrode sheet.

[0038] In some embodiments of the present application, the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound, laminated or the like to obtain a battery cell and manufacture a lithium-ion battery.

[0039] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector layer and a positive electrode active material layer which are arranged in sequence.

[0040] In some embodiments of the present application, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.

[0041] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, which is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese aluminum oxide.

[0042] In some embodiments of the present application, the raw material of the positive electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.

[0043] In some embodiments of the present application, the positive electrode active material layer includes 70 to 99 wt % of the positive electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.

[0044] In some embodiments of the present application, the electrolyte may be at least one of a solid electrolyte or an electrolyte.

[0045] In some embodiments of the present application, the electrolyte includes an electrolyte salt and an organic solvent, wherein the specific types and compositions of the electrolyte salt and the organic solvent are not subject to specific limitations.

[0046] In some embodiments of the present application, the electrolyte further includes additives, such as at least one of positive electrode film-forming additives, negative electrode film-forming additives, and cycle improving and low temperature additives.

[0047] In some embodiments of the present application, the separator comprises a polymer separator, and the polymer separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, and multilayer composite films thereof.

[0048] According to a third aspect of the present application, there is provided an electrical device, the electrical device comprising the aforementioned lithium-ion battery.

[0049] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0050] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0051] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0052] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0053] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0054] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0055] The present application is described below in conjunction with specific embodiments.

[0056] Examples 1 to 12

[0057] Embodiments 1 to 12 respectively provide a negative electrode sheet and a lithium-ion battery made of the negative electrode sheet.

[0058] The preparation process of the negative electrode sheet is as follows:

[0059] (1) A negative electrode active material, a conductive agent (mixed with conductive carbon black SP and carbon nanotubes CN in a mass ratio of 9:1), and a binder (mixed with styrene-butadiene rubber SBR and sodium polyacrylate PAA in a mass ratio of 5:18) were mixed in a weight ratio of 97.7:1.1:1.2 to prepare a negative electrode active material slurry.

[0060] (2) The negative electrode active material slurry is evenly coated on both sides of the negative electrode current collector copper foil, and then dried, cold pressed, and cut into strips to obtain the negative electrode sheet.

[0061] Among them, the negative electrode active material is silicon carbon particles and graphite, the graphite material is purchased from Shanshan New Materials Co., Ltd., model DM-APG-0017-0002, and the silicon carbon particles (silicon oxide with a carbon coating of about 10wt%) are purchased from Jinsi Technology Co., Ltd., model YP-APS-0090-0000. The proportion of silicon carbon particles in the negative electrode active material and the various parameters of the current collector copper foil are shown in Table 1.

[0062] The preparation process of the positive electrode is as follows:

[0063] (1) LiCoO2, conductive agent acetylene black, conductive agent carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed in an N-methylpyrrolidone solvent system at a weight ratio of 97.6:0.5:0.6:1.3 to obtain a positive electrode active material slurry.

[0064] (2) The prepared positive electrode active material slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut into strips to obtain positive electrode sheets.

[0065] The isolation membrane is a polyethylene (PE) membrane with a ceramic compound coated on the surface.

[0066] The electrolyte is a 1 mol / L LiPF6 solution of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) in a volume ratio of 1.2:1:4:4.

[0067] The whole battery preparation process is as follows: the positive electrode sheet, the isolation film, and the negative electrode sheet are wound into a bare battery cell, and then packaged and injected with electrolyte to finally obtain a finished lithium-ion battery.

[0068] In addition, comparative examples 1 to 6 are provided, which differ from the above-mentioned embodiment in that the silicon doping ratio of the negative electrode sheet and the parameters of the negative electrode current collector are different, as shown in Table 1 for details.

[0069] Among them, the detection method of the grain size D of the current collector copper foil is as follows:

[0070] Tested by X-ray diffractometer (XRD).

[0071] The test method for the tensile strength of the current collector copper foil is as follows:

[0072] The copper foil was cut into small pieces with a width of 15 mm and a length of 120 mm and tested using a tensile tester.

[0073] The test method for the elongation of the current collector copper foil is as follows:

[0074] The sample size is 13mm×150mm, and it is baked at 150℃ for 2 hours. It is tested using a plasticity testing machine with a moving rate of 0.05mm / mm~0.5mm / mm per minute. The elongation is calculated using the following formula: elongation=(length after stretching-length before stretching) / length before stretching×100%.

[0075] The method for testing the elastic modulus of the current collector copper foil is as follows:

[0076] The sample size is 2mm×25mm. It is tested using a tensile tester. The stress F and strain x are recorded. According to Hooke's law formula k=F / x, the proportionality coefficient k, which is the elastic modulus, is calculated.

[0077] Table 1. Parameter comparison of examples and comparative examples

[0078] Serial number W / % T / μm D / μm λ S / Mpa A / % C / Gpa (31.7λ+15) / (2930W) (18W+42) / C Example 1 5.0 5.0 1.50 3.3 320 6.2 70 0.82 0.61 Example 2 15.0 5.0 1.50 3.3 320 6.2 70 0.27 0.64 Example 3 20.0 5.0 1.50 3.3 320 6.2 70 0.21 0.65 Example 4 5.0 4.0 1.50 2.7 300 5.4 70 0.68 0.61 Example 5 5.0 7.0 1.50 4.7 550 7.0 70 1.11 0.61 Example 6 5.0 9.0 1.50 6.0 670 9.7 70 1.40 0.61 Example 7 5.0 5.0 0.15 33.3 530 3.0 70 7.32 0.61 Example 8 5.0 5.0 3.80 1.3 280 7.3 70 0.39 0.61 Example 9 5.0 5.0 1.50 3.3 320 6.2 50 0.82 0.86 Example 10 5.0 5.0 1.50 3.3 320 6.2 90 0.82 0.48 Embodiment 11 5.0 5.0 1.00 5.0 350 14.6 70 1.18 0.61 Example 12 5.0 8.0 0.30 26.7 900 7.5 70 5.87 0.61 Comparative Example 1 5.0 4.0 4.00 1.0 240 5.8 70 0.32 0.61 Comparative Example 2 5.0 4.0 0.08 50.0 590 1.8 70 10.92 0.61 Comparative Example 3 15.0 5.0 2.50 2.0 290 6.6 70 0.18 0.64 Comparative Example 4 5.0 5.0 0.13 38.5 660 2.5 70 8.42 0.61 Comparative Example 5 5.0 5.0 0.13 38.5 660 2.5 110 8.42 0.39 Comparative Example 6 20.0 5.0 0.13 38.5 660 2.5 50 2.11 0.91

[0079] The performance of the negative electrode sheets and lithium batteries of the embodiments and comparative examples were tested by the following methods:

[0080] (1) Cycle test

[0081] In an environment of 25℃, the cycle test was carried out according to the following method: charging mode: 2.8C CC to 4.27V, 2C CCto4.35V, CV to 1.8C, 1.8C CC to 4.45V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2C CC to4.55V, CV to 0.25C; discharging mode: 0.7C DC to 3.0V.

[0082] 500-cycle capacity retention rate = discharge capacity at the 500th cycle / discharge capacity at the 1st cycle × 100%;

[0083] Thickness expansion rate after 500 cycles = (full-power thickness at the 500th cycle - initial half-power thickness) / initial half-power thickness × 100%;

[0084] The battery thickness is tested using a 600PPG thickness gauge.

[0085] (2) Pole brittleness test

[0086] At 25℃, cycle for 300 cycles as follows: charging mode: 2.8C CC to 4.27V, 2CCC to 4.35V, CV to 1.8C, 1.8C CC to 4.45V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2C CC to 4.55V, CV to 0.25C; discharging mode: 0.7C DC to 3.0V. Disassemble the battery in the fully charged state, remove the negative electrode sheet, and check the fracture of the corner of the negative electrode sheet with naked eyes.

[0087] Table 2. Performance tests of examples and comparative examples

[0088]

[0089]

[0090] Comparing Examples 1 to 3, as the silicon doping amount W increases, the volume expansion becomes more obvious, the capacity retention rate after 500 cycles gradually decreases, and the thickness expansion rate gradually increases.

[0091] Comparing Examples 1 and 4 to 6, as the thickness T of the current collector increases, the thickness grain size ratio λ gradually increases, the tensile strength and elongation also increase continuously, the capacity retention rate after 500 cycles gradually increases, and the thickness expansion rate gradually decreases.

[0092] Comparing Examples 1, 7, and 8, as the grain size D of the current collector gradually increases, the thickness grain size ratio λ gradually decreases, the tensile strength gradually decreases, the elongation gradually increases, the capacity retention of 500 cycles first increases and then decreases, and the thickness expansion first decreases and then increases.

[0093] Comparing Examples 1, 9, and 10, as the elastic modulus increases, the capacity retention at 500 cycles first increases and then decreases, and the thickness expansion first decreases and then increases.

[0094] Comparing Examples 1, 11, and 12, with the continuous adjustment of the current collector thickness T and the current collector grain size D, the value of (31.7λ+15) / (2930W) gradually increases, the capacity retention of 500 cycles first increases and then decreases, and the thickness expansion first decreases and then increases.

[0095] Comparing Example 1 and Comparative Example 1, when the grain size D of the current collector is too large, the tensile strength decreases, and it is difficult to balance the expansion stress of the negative electrode sheet during the charge and discharge process, resulting in a significant decrease in its capacity retention rate and a thickness expansion rate that almost doubles.

[0096] Comparing Example 1 and Comparative Example 2, when the grain size D of the current collector is too small and the value of (31.7λ+15) / (2930W) is too large, although the tensile strength is still maintained at a certain level, the elongation of Comparative Example 2 is low, the expansion stress of the negative electrode sheet during the charge and discharge process cannot be solved, the decrease in capacity retention rate and the increase in thickness expansion rate are more obvious than those in Comparative Example 1, and after 300 cycles, the electrode corners of Comparative Examples 2 and 4 are broken.

[0097] Comparing Example 1 with Comparative Example 3, increasing the silicon doping amount and the grain size of the current collector, the tensile strength of the current collector decreases, the value of (31.7λ+15) / (2930W) is too low, the capacity retention rate decreases significantly, and the thickness expansion rate increases by more than 300%.

[0098] Comparing Example 1 and Comparative Example 4, although the ratios of the current collector and the negative electrode active material are both within the normal range, when the value of (31.7λ+15) / (2930W) is too large, the decrease in capacity retention rate and the increase in thickness expansion rate are still quite obvious, and the pole piece breaks occur.

[0099] Comparing Example 1 and Comparative Example 5, when the value of (31.7λ+15) / (2930W) is too large and the value of (18W+42) / C is too small, the decrease in capacity retention rate and the increase in thickness expansion rate are still obvious, and the electrode breakage phenomenon occurs.

[0100] Comparing Example 1 with Comparative Example 6, when the value of (18W+42) / C is too large, the battery still has obvious cycle performance degradation and electrode breakage.

[0101] It can be seen from Examples 1 to 12 and Comparative Examples 1 to 6 that this solution has good cycle performance. The degree of deformation of the battery can be characterized by the expansion rate. The high-strength, low-elongation current collector breaks during the cycle, resulting in a decrease in the capacity retention rate and a sharp increase in expansion; while low-strength, high-elongation will cause the battery to deform and precipitate lithium, and the capacity retention rate and expansion will also be deteriorated. Therefore, satisfying the relationship: 0.2≤(31.7λ+15) / (2930W)≤7.5 and 0.4≤(18W+42) / C≤0.9 can make the tensile strength and elongation of the current collector better balance the expansion stress of the negative electrode sheet during the charge and discharge process, improve the mechanical reliability of the negative electrode sheet, and avoid the fracture and deformation of the sheet during long cycles; thereby improving the long-cycle performance of the battery and extending the battery life.

[0102] Embodiment 13

[0103] This embodiment provides a negative electrode sheet and a lithium ion battery made of the negative electrode sheet. The difference from Embodiment 1 is that the silicon-carbon particles in the negative electrode active material are replaced with an equal mass of elemental silicon.

[0104] Embodiment 14

[0105] This embodiment provides a negative electrode sheet and a lithium ion battery made of the negative electrode sheet. The difference from Embodiment 1 is that the silicon-carbon particles in the negative electrode active material are replaced with an equal mass of Si-Fe alloy.

[0106] Embodiment 15

[0107] This embodiment provides a negative electrode sheet and a lithium ion battery made of the negative electrode sheet. The difference from Embodiment 1 is that the silicon-carbon particles in the negative electrode active material are replaced by silicon dioxide particles of equal mass without a carbon coating layer.

[0108] The negative electrode sheets in Examples 13 to 15 satisfy Formula I and Formula II, and are tested to have similar capacity retention and thickness expansion rates as those in Example 1 after 500 cycles, and no fractures are found at the corners of the electrode sheets after 300 cycles.

[0109] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector layer and a negative electrode active material layer arranged in sequence, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material, and the negative electrode sheet satisfies Formula I: 0.2≤(31.7λ+15) / (2930W)≤7.5; Wherein, λ=T / D, T is the thickness of the negative electrode current collector layer, and D is the grain size of the negative electrode current collector layer; W is the mass percentage of the silicon-based material to the negative electrode active material.

2. The negative electrode sheet according to claim 1, characterized in that: 1<λ≤40.

3. The negative electrode sheet according to claim 2, characterized in that: T is 4~9μm, and D is 0.1~3.8μm.

4. The negative electrode sheet according to claim 1, characterized in that: 3%≤W≤30%。 5. The negative electrode sheet according to claim 1, characterized in that: The negative electrode sheet also satisfies Formula II: 0.4≤(18W+42) / C≤0.9; Wherein, C is the elastic modulus of the negative electrode current collector layer.

6. The negative electrode sheet according to claim 5, characterized in that: 50GPa≤C≤120GPa.

7. The negative electrode sheet according to claim 1, characterized in that: The tensile strength of the negative electrode current collector layer is 250-900 MPa, and / or the elongation of the negative electrode current collector layer is 2-15%.

8. The negative electrode sheet according to claim 1, characterized in that: The silicon-based material includes at least one of elemental silicon, silicon-carbon material, silicon-oxygen material, and silicon alloy, and / or the negative electrode current collector layer includes at least one metal element of copper, nickel, and titanium.

9. A lithium-ion battery, characterized in that A negative electrode sheet comprising any one of claims 1 to 8.

10. Electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Negative electrode for lithium-ion secondary battery and lithium-ion secondary battery

    CN103367700A

  • Negative current collector, negative pole piece and electrochemical device

    CN110943228A

  • Negative current collector, negative pole piece, electrochemical device, and electric vehicle and electronic product comprising electrochemical device

    CN113363499A

  • Lithium ion battery

    CN115377352A

  • Negative plate and battery

    CN118156412A

Cited By

  • Negative pole piece, preparation method thereof and lithium ion battery

    CN120878757A